1998
DOI: 10.1093/jmedent/35.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Black Fly Species (Diptera: Simuliidae) on an Amerindian Reservation with a High Prevalence of Fogo Selvagem to Neighboring Disease-Free Sites in the State of Mato Grosso do Sul, Brazil

Abstract: Fogo selvagem is an autoimmune blistering skin disease that principally occurs among rural Brazilians living in geographically clumped disease foci. Exposure to hematophagous black flies possibly is related to the cause of the disease. We compared the occurrence, proportions, and richness of simuliid species immatures and the biting activity of adult females within a recently discovered, high prevalence focus of fogo selvagem, the Limão Verde Terena Reservation, to that of neighboring regions with no reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
15

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 0 publications
0
43
0
15
Order By: Relevance
“…Inhibitory signals produced by the PD-1/PD-L pathway are of crucial relevance to the mechanisms maintaining tolerance and to terminate immune response in peripheral tissues, thus limiting organ damage (Freeman et al, 2000;Latchman et al, 2001;). The causes of initiation and perpetuation of the auto-aggressive responses in pemphigus foliaceus patients are largely unknown, although there is consensus about the influence of both genetic and environmental factors on susceptibility to this condition (Eaton et al, 1998;Petzl-Erler and Santamaria, 1989). The pathogenic concepts include defects in the maintenance of peripheral immune tolerance towards potential autoantigens (Coyle and Gutierrez-Ramos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory signals produced by the PD-1/PD-L pathway are of crucial relevance to the mechanisms maintaining tolerance and to terminate immune response in peripheral tissues, thus limiting organ damage (Freeman et al, 2000;Latchman et al, 2001;). The causes of initiation and perpetuation of the auto-aggressive responses in pemphigus foliaceus patients are largely unknown, although there is consensus about the influence of both genetic and environmental factors on susceptibility to this condition (Eaton et al, 1998;Petzl-Erler and Santamaria, 1989). The pathogenic concepts include defects in the maintenance of peripheral immune tolerance towards potential autoantigens (Coyle and Gutierrez-Ramos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Todos os pontos foram amostrados apenas uma vez, e os espécimes coletados manualmente em um trecho de 100 metros de cada corpo d'água. A segunda fonte de informação foi a consulta de trabalhos publicados (Eaton et al, 1998;Hamada & Adler, 1999;Coscarón & Coscarón-Arias, 2007;Adler & Crosskey, 2015). Dada a importância de disponibilizar informações sobre a distribuição das espécies, foram incluídas no checklist todas as localidades de ocorrência dentro do estado.…”
Section: Methodsunclassified
“…De acordo com Adler & Crosskey (2015) existem atualmente 2.177 espécies de Simuliidae válidas (incluindo 12 fósseis) das quais aproximadamente 360 são encontradas na Região Neotropical (Currie & Adler, 2008), sendo 92 (Adler & Crosskey, 2015;Hamada et al, 2015) (Eaton et al, 1998;Adler & Crosskey, 2015).…”
unclassified
“…16 It is hypothesized that a break of immune tolerance follows exposure to some environmental factor(s) that include hematophagous insect bites, as reported elsewhere. 16,23,24 The potential role of black fly triggering the autoimmune response in FS is supported by two main studies: exposure to simuliid bites as a risk factor for FS (4.7 odds ratio), 23 and the predominance of a certain black fly species (Simulium nigrimanum) in endemic areas, when compared with non-endemic areas of the Brazilian coast. 24 Additional data on the environment triggers is suggested by Aoki and others, 16 who reported a high frequency of black fly (87%), kissing bugs (67%), and bed bugs (60%) bites in FS patients, and showed that precarious living conditions represented a significant risk factor for FS.…”
Section: Introductionmentioning
confidence: 96%